FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI PEKERJA WANITA DALAM GERAKAN PEKERJA PEREMPUAN SEHAT DAN PRODUKTIF (GP2SP) - Susanti, Ariani; Budiati, Endang; Rahayu, Dewi; Pramudho, Kodrat (LPPMK STIKES Widyagama Husada, 2025)
The impact of worker inactivity in GP2SP (Gerakan Pekerja Perempuan Sehat dan Produktif) includes not receiving education and facilities supporting workers' physical and mental health, unmet gender equality in the workplace, and hindered personal development, quality of life, and work productivity. Interview results revealed that only 65% of the GP2SP program's target has been achieved out of 3,000 workers. The purpose of this research is to analyze the factors related to the participation of female workers in the GP2SP. This quantitative study uses a cross-sectional design. The research sample consists of 101 respondents, selected through purposive sampling technique. The results showed a relationship between knowledge with a p-value of 0.010, workers' attitudes with a p-value of 0.021, family support with a p-value of 0.013, social support with a p-value of 0.036, and the role of the GP2SP team in the workplace with a p-value of 0.023. Among these, family support is dominantly related to worker participation in GP2SP with a p-value of 0.023 and an OR of 6.348. It is suggested to plan a mayoral policy to strengthen family support involving all sectors and fields through health education, communication, and guidance to the families of female workers.